A new auto-regressive (AR) model-based algorithm for motion picture restoration - Kalra, S.; Chong, M.N.; Krishnan, D. (1997 IEEE International Conference on Acoustics, Speech, and Signal Processing, 1997)
This paper proposes a new AR model-based restoration algorithm which is able to suppress mixed noise processes and recover lost signals in an image sequence. A drawback of an AR model is the limiting size of the block (of pixels) that can be adequately modeled. Using a single set of AR coefficients to restore a large region of missing data will result in a homogenized texture region. In order to overcome this inherent limitation of the AR model, a block-based divide-and-conquer approach is proposed. In addition, a new Gaussian weighting scheme is used to better estimate the AR coefficients for the interpolation process.